PENGARUH KEDISIPLINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN FOOD & BEVERAGE SERVICE DI HOTEL SINTESA PENINSULA MANADO - Siswa Dwi Rahayu; Nardiansyah Kamumu; Sonny Wijanarko (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2022)
This study aims to find out how the influence of discipline and work environment on the performance of food & beverage service employees at the Sintesa Peninsula Hotel Manado. The research method used is the Quantitative Method, with the Multiple Linear Regression data analysis technique. The results of the study prove that Discipline has a positive and significant impacts on Food and Beverage Service Employee Performance with a regression coefficient value of 3.264 and a significance of 0.009. This shows that the higher the Employee Work Discipline, the higher the Employee Performance will be. The work environment has a positive and significant impact on Food and Beverage Service Employee Performance with a regression coefficient of 2.530, and a significance of 0.0144. This shows that the better the hotel work environment, the better the employee performance will be. Discipline and work environment have a significant influence on the performance of Food and Beverage Service employees with an F-count of 6,493 and a significance of 0.008. This shows that the better the Discipline and Work Environment, the more Employee Performance will increase. The conclusion of this study is that Discipline and Work Environment have a significant influence on Food and Beverage Service Employee Performance. The advice given is that the Sintesa Peninsula Manado Hotel must provide awareness to employees regarding the importance of compliance or discipline and do several things to improve the work environment.